Cytokine profiles in severe SARS-CoV-2 infection requiring extracorporeal membrane oxygenation support. (2021) - Kaman, Kelsey; Azmy, Veronica; Chichra, Astha; Britto-Leon, Clemente; Price, Christina
Abstract: It has been postulated that the underlying pathophysiology of COVID-19 is mediated by cytokine storm resulting in a hyperinflammatory state. A similar kind of cytokine-storm has been described in individuals undergoing veno-venous extracorporeal membrane oxygenation (VV ECMO) support. There is therefore concern that initiation of VV ECMO support among COVID19 patients could further exacerbate this dysregulated inflammatory response. In this prospective cohort study, we describe the clinical course and cytokine fluctuations in eight subjects treated with VV ECMO for management of refractory respiratory failure from COVID19. Among all eight patients, cytokine elevations were noted among Interleukin 6 (IL-6), Interleukin 10 (IL-10), and Interleukin 2 Receptor (CD25) soluble (sIL2R). Although further research is necessary, among our cohort of patients it did not appear that initiation of VV ECMO worsened cytokine storm.